Application of Whatman FTA card method in oil palm DNA extraction and PCR analysis / Wan Nurhayati Wan Hanafi and Nur Syahirah Abu Bakar - Wan Hanafi, Wan Nurhayati; Abu Bakar, Nur Syahirah (Penerbit UiTM (UiTM Press), 2019)
Polymerase Chain Reaction (PCR) analysis in the study of oil palm DNA generally carried out by using DNA template obtained from grinding of leaf samples in liquid nitrogen followed by hexadecyltrimethylammonium bromide (CTAB) protocol. The present study explores the FTA card as a method to retrieve PCR-amplifiable oil palm DNA. Oil palm leaves were cut and crushed before deposited onto the FTA card. An attempt was made by amplifying the EgSHP gene using a punch of FTA card as a DNA template. The successful outcome of PCR was measured by the presence of PCR amplicons on 1% agarose gel electrophoresis, indicate the genotype of oil palm fruit form. This present study demonstrates that the FTA card provides a versatile alternative to the study of oil palm genetics.